Differentiating between self and others: An ALE meta-analysis of fMRI studies of self-recognition and theory of mind - van Veluw, S; Chance, SA (2014)
The perception of self and others is a key aspect of social cognition. In order to investigate the neurobiological basis of this distinction we reviewed two classes of task that study self-awareness and awareness of others (theory of mind, ToM). A reliable task to measure self-awareness is the recognition of one's own face in contrast to the recognition of others' faces. False-belief tasks are widely used to identify neural correlates of ToM as a measure of awareness of others. We performed an activation likelihood estimation meta-analysis, using the fMRI literature on self-face recognition and false-belief tasks. The brain areas involved in performing false-belief tasks were the medial prefrontal cortex (MPFC), bilateral temporo-parietal junction, precuneus, and the bilateral middle temporal gyrus. Distinct self-face recognition regions were the right superior temporal gyrus, the right parahippocampal gyrus, the right inferior frontal gyrus/anterior cingulate cortex, and the left inferior parietal lobe. Overlapping brain areas were the superior temporal gyrus, and the more ventral parts of the MPFC. We confirmed that self-recognition in contrast to recognition of others' faces, and awareness of others involves a network that consists of separate, distinct neural pathways, but also includes overlapping regions of higher order prefrontal cortex where these processes may be combined. Insights derived from the neurobiology of disorders such as autism and schizophrenia are consistent with this notion. © 2013 Springer Science+Business Media New York.